Dosis de gallinaza en el aporque en las características agronómicas y rendimiento en Lactuca sativa L., Var. great lakes. Loreto. 2023 - Pezo Villacorta, Xiomi Carolina (2024)
The hilling is a cultural task that is performed in many cultivated plants and consists of accumulating soil at the foot of the plant, mainly to provide greater stability, control pests, diseases and maintain greater soil moisture. Along with this work, in some crops such as lettuce, fertilization is used to improve yields. The objective of this study was to evaluate the effect of different levels of organic fertilizer applied in the hilling on the agronomic characteristics and yield of Lactuca sativa L., var. Great Lakes in Zungaro Cocha, San Juan - 2023. The study was conducted at the Horticultural Plants Workshop, Faculty of Agronomy-UNAP. A completely randomized block design (CRBD) was used with 4 treatments consisting of different doses of poultry manure (T0: 0, T1: 1, T2: 2, T3: 3 kg.m-2) at the time of hilling and with 4 replications. American lettuce variety Great Lakes was used. After analysis of the results, the main conclusions were that the different doses of poultry manure applied at the time of hilling did not significantly influence the agronomic characteristics of plant height, plant extension, head diameter and head height. However, there were significant differences for root mass, stem mass, head mass and total plant mass. With the T3 treatment (3 kg.m-2), lower root mass (6.16 g) and higher stem mass (38.89 g), head/plant mass (349.16 g) and total plant mass (394.25 g) were obtained. It also allowed estimating the maximum yield at 39,106 kg.ha-1 of heads of American lettuce var. Great Lakes. For each kg of poultry manure applied at the time of hilling, there is an increase of 29.7 g of head/plant mass.